ACCULTURATION OF PERANAKAN CULTURE IN THE DIVERSITY OF LAKSA MENU IN SOUTHEAST ASIA - Nugroho, Akbar Haryo (International Review of Humanities Studies, 2023)
The Peranakan refers to one ethnic group that originated from many Chinese ethnicities that intermarriage and assimilated with local people in many places in Southeast Asia. They bring many inventions, which enriched cultures and heritages in many Southeast Asian places. One of the most well-known cuisines from Peranakan birth is a Laksa. Laksa is a complex dish consisting of noodles, a side dish usually consisting of seafood, chicken, or egg, and savory broth with many spices and herbs. Laksa can be found in many Southeast Asian countries, especially places with a significant Chinese descendent population. The diversity of the laksa menu is a major marker of the influence of the Peranakan culinary culture in Southeast Asia.